Conceptions of Interculturality and classroom practice: A Study with Teachers of Shipibo Communities in Perú - Cépeda García, Nora (2019)
This article presents the results from a qualitative and comparative study. The general objective was to identify the conceptions of interculturality of teachers in two intercultural bilingual Shipibo-Spanish schools in Lima and Ucayali, and describe how they are incorporated in their teaching practices and curricular planning. The methodology included a semi-structured interview, classroom observations, and the analysis of learning units. Findings resulted from a process of data reduction and triangulation. Prevalent themes were: the affirmation of their own culture, the encounter with other languages and cultures, and the exchange among cultures. There was a relation between teachers’ conceptions and their classroom practices. Regarding curricular planning, there were differences in the incorporation of contents with an intercultural perspective between the schools in Lima and Ucayali.